Sensitivity of Bacteria causing Hospital-Acquired Pneumonia (HAP) in the Intensive Care Unit (ICU) to Empiric Antibiotics - APRILIANY, FITRI; Umboro, Recta Olivia; Ersalena, Vera Fitriya; Setiawan, Deni; Cholisah, Elis (Universitas Borneo Lestari, 2025)
The main therapy for the treatment of pneumonia is antibiotics. The use of antibiotics requires special attention to prevent antibiotic resistance. Therefore, it is important to know the pathogenic microorganisms that cause hospital-acquired pneumonia (HAP) infections. This study aimed to describe the sensitivity of negative-positive bacteria to empiric antibiotics in HAP patients. The study method was an analytical descriptive observational study with a cross-sectional design. Data were collected from patient medical records for the period January 2019 – December 2020. Inclusion criteria were ICU patients diagnosed with HAP, aged 15 years, with complete medical records (age, sputum culture, leukocytes, chest x-ray results), treatment history and outcome parameters (vital signs). Exclusion criteria were pregnant patients, involuntary discharge, and ICU stay of less than 48 hours. The data in this study were analyzed descriptively and Likelihood Ratio. The results of the description showed that the empiric antibiotics with sensitivity more than 70% against gram-positive bacteria causing HAP were rifampin (78%), TMP-sulfamethoxazole (78%), vancomycin (100%), and linezolid (100%) while the empiric antibiotics with sensitivity more than 70% against gram-negative bacteria was cefoperazone-sulbactam (≥75%), followed amikacin and imipenem (≥55%). Meanwhile, the empiric antibiotics had a very low sensitivity (≤ 50%) against ESLB-producing bacteria and MRSA. There is a significant relationship between age and educational level factors and bacterial growth in sputum cultures (p<0.05). Conclusion: Vancomycin and linezolid are sensitive to gram-positive bacteria, cefoperazone-sulbactam is sensitive to gram-negative bacteria and resistance to ESLB-producing bacteria and MRSA has occurred.